Studies on the Bulbs of Urginea indica - Beri, R. M.; Pharasi, S. C. (Indian Forester, 1971)
The proximate analysis of Urginea indica bulb powder and that of the mucilage isolated from its 2 per cent solution by precipitation with alcohol is described. It contains approx. 51 per cent of the mucilage. Properties of the mucilage have been described and compared with substances having similar properties. Bulb powder and the mucilage possess a very high swelling power in water. Viscosities of their solutions at different concentrations, and the effect of temperature on viscosity is described. Bulb powder possesses good adhesive properties. It was tried as a thickening material in Calico Printing and has indicated great possibilities for its use as a thickening agent for colours to be used in screen printing of textiles.